2018
DOI: 10.1016/j.jrp.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

An emic-etic approach to personality assessment in predicting social adaptation, risky social behaviors, status striving and social affirmation

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
0
6
0
2
Order By: Relevance
“…Furthermore, interpersonal relatedness had a small incremental validity for job performance over a Western measure of mental ability in Chinese immigrant workers in Romania, but no incremental validity in Romanian workers (Ion et al, 2016). Finally, in one of the few studies of incremental predictive validity beyond Asia, Burtăverde et al (2018) found that a lexically derived personality instrument in Romania explained variance in socially adaptative behaviors and outcomes above the Big Five and the HEXACO model. This line of research has drawn attention to the potential of indigenously derived concepts to explain variation in relevant outcomes across cultures.…”
Section: Integrating Perspectives: From Indigenous To Emic–eticmentioning
confidence: 98%
“…Furthermore, interpersonal relatedness had a small incremental validity for job performance over a Western measure of mental ability in Chinese immigrant workers in Romania, but no incremental validity in Romanian workers (Ion et al, 2016). Finally, in one of the few studies of incremental predictive validity beyond Asia, Burtăverde et al (2018) found that a lexically derived personality instrument in Romania explained variance in socially adaptative behaviors and outcomes above the Big Five and the HEXACO model. This line of research has drawn attention to the potential of indigenously derived concepts to explain variation in relevant outcomes across cultures.…”
Section: Integrating Perspectives: From Indigenous To Emic–eticmentioning
confidence: 98%
“…1. Экстраверсия (Extraversion В кросс-культурном контексте существуют два основных подхода к идентификации черт личности (например: Burtăverde et al, 2018). Согласно первому (emic) подходу, необходимо определить те компоненты личности, которые являются культурно-специфическими.…”
Section: методика Big Five Inventory-2unclassified
“…В кросс-культурном контексте существуют два основных подхода к идентификации черт личности (например: Burtăverde et al, 2018). Согласно первому (emic) подходу, необходимо определить те компоненты личности, которые являются культурно-специфическими.…”
Section: ен осинunclassified